PENGARUH INVESTASI FISIK DAN INVESTASI PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI JAWA TIMUR 1990-2004 - Sjafii, Achmad (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
The Â roles Â of Â physical Â investment Â and Â government Â expenditure Â on Â economicdevelopment has been acknowledged in any various research. However, the study inthe role of human capital investment on development economic just Â three decadeslater has been held. Human capital investment could be in the form of governmentexpenditure, mainly Â to Â increase Â the Â quality Â of Â human Â resources. Â It Â consist Â ofexpenditure Â for Â the Â health Â and Â education. Â It Â is Â an Â importance Â factor Â to Â increasehuman development Â quality Â and Â enhance economic Â growth. The Â purposes of Â thisresearch are to determine the influences of [1] private investment; [2] labor forcegrowth; Â [3] Â government Â expenditure Â of Â East Â Java Â Province Â for Â human Â capitalinvestment; [4] government expenditure of East Java Province Â for routine/annualexpenditure; and [5] external condition on economic growth of East Java Province.The research applies panel data analysis, and it combines the cross section data in37 regency/municipality and time series data for periods 1990-2004. The researchapplies the verification process that is the Hausman test. The verification test foundthat the suitable model is fixed effect (FE) model. It is found in this research that allthe Â independent variables except â€œexternal Â conditionâ€ variable have statisticallypositive and significant influence on the economic growth in East Java Province.Keywords: economic growth, physical investment and human capital investment.